2013
DOI: 10.1002/ajhb.22495
|View full text |Cite
|
Sign up to set email alerts
|

2D:4D Ratio in children at familial high‐risk for eating disorders: The role of prenatal testosterone exposure

Abstract: ObjectivesMarkers of prenatal hormone exposure have been associated with the development of eating disorder (ED) behaviors. Our aim was to determine whether 2D:4D ratio, a marker for in utero testosterone exposure, is associated with risk for ED in a large population-based cohort: the Avon Longitudinal Study of Parents and Children (ALSPAC).MethodsThis is the first study to investigate prenatal testosterone exposure in children at high-risk for ED, using 2D:4D as a marker. We compared children whose mothers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
1
20
0
3
Order By: Relevance
“…By contrast, some studies have shown opposite effects of prenatal testosterone exposure on eating disorder risk. For example, lower 2D:4D ratios were observed among daughters of women with lifetime BN compared to daughters of unaffected mothers . No significant differences were observed in sons.…”
Section: Prenatal Risk Factors Of Eating Disordersmentioning
confidence: 87%
See 1 more Smart Citation
“…By contrast, some studies have shown opposite effects of prenatal testosterone exposure on eating disorder risk. For example, lower 2D:4D ratios were observed among daughters of women with lifetime BN compared to daughters of unaffected mothers . No significant differences were observed in sons.…”
Section: Prenatal Risk Factors Of Eating Disordersmentioning
confidence: 87%
“…For example, lower 2D:4D ratios were observed among daughters of women with lifetime BN compared to daughters of unaffected mothers. 23 No significant differences were observed in sons. Another study 24 found lower 2D:4D ratios (i.e., higher prenatal testosterone) in women with AN compared to women with BN, with control individuals intermediary.…”
Section: Prenatal Sex-hormone Effectsmentioning
confidence: 87%
“…All participants in the study about hirsutism who were diagnosed with an eating disorder were diagnosed with PCOS . Interestingly, daughters of mothers who had lifetime BN had a lower ratio of the second and fourth digits of the hand (2D:4D), which is associated with high levels of fetal testosterone relative to fetal estradiol and indicates the daughters had had higher testosterone exposure . This may indicate androgens as a link between BN, PCOS, menstrual disturbances, and fertility issues.…”
Section: Resultsmentioning
confidence: 99%
“…80 Interestingly, daughters of mothers who had lifetime BN had a lower ratio of the second and fourth digits of the hand (2D:4D), which is associated with high levels of fetal testosterone relative to fetal estradiol and indicates the daughters had had higher testosterone exposure. 57 This may indicate androgens as a link between BN, PCOS, menstrual disturbances, and fertility issues. There is evidence that testosterone stimulates appetite, high circulating levels of this testosterone in women have been associated with impaired impulse control, irritability and depression, and antiandrogenic treatment reduces bulimic behaviors.…”
Section: Binge Eating Disordermentioning
confidence: 99%
“…In contrast, views on their effects in eating disorders (ED) are mixed. Specifically, it has been suggested that high prenatal T exposure would have neuroprotective effects (Baker et al, ; Culbert et al, ; Klump et al, ), but also that it contributes to the development of EDs, especially anorexia and bulimia nervosa as demonstrated by the 2D:4D ratio (Kothari et al, ; Quinton et al, ). Regarding animal research, it has been suggested that early exposure to high T during development is related to masculinization in food intake and body weight in female rats (Culbert et al, ).…”
Section: Introductionmentioning
confidence: 99%